OCCURRENCE OF PHILLIPSITE MINERAL IN SUB- SEAFLOOR OF ROO RISE-INDIAN OCEAN : A TECTONIC EROSION SYNTHESIS - Dida Kusnida (Puslitbang tekMIRA, 2009)
A single deep-sea core (MD982156) of 30.30 meters long which is obtained during the MD III-IMAGES IV Expedition from Roo Rise - Indian Ocean in 1998 was studied. Down to 30 meters of the core length, the sediment consists of abundance planktonic foraminiferas. Below 30 meters, it is mostly composed of phillipsite mineral-rich sediment that is associated with nannoplanktons.The Paleocene authigenic phillipsite minerals associated with nannoplanktons is separated from Late Miocene to Holocene planktonic foraminiferas rich-sediments by hiatus. This hiatus or non deposi- tional in Roo Rise suggest be triggered by long Cenozoic tectonic erosion.